VD_FINDINFO HC / 2017 / 536 vom 23. Juni 2017 - VD Tribunal cantonal (2017)
DÉCISION D'EXTENSION, SÛRETÉS, ASSISTANCE JUDICIAIRE, INSOLVABILITÉ | 118 al. 1 let. a CPC (CH), 119 al. 2 CPC (CH), 119 al. 3 CPC (CH), 99 al. 1 let. b CPC (CH)